A review of printable, flexible and tissue equivalent materials for ionizing radiation detection. (30th November 2021) - Posar, Jessie A; Petasecca, Marco; Griffith, Matthew J
Abstract: Advances in flexible and printable electronics have paved the way for large-area, and low-cost wearable electronics that will revolutionize the way we detect and monitor ionizing radiation. The improvements to early detection and widespread use of treatment procedures of tumors and other illnesses using ionizing radiation have led to the rapid increase in the yearly dose exposure to the public. Therefore, safety organizations must introduce stricter quality assurance measures to ensure the safe delivery of the total dose to the patient—only achievable using live monitoring systems, named in-vivo dosimetry. Such systems would also benefit the safety of professional personnel employed in areas that encounter higher exposures of ionizing radiation including nuclear plants, space exploration, flight staff, and research beamline facilities. However, the current real-time detectors employ expensive and rigid high-Z materials including silicon, germanium, and cadmium telluride, that suffer substantial limitations in monitoring the dose deposited in biological tissue and conforming to the complex contours of the human body over large areas. We provide insights into the innovative materials capable of solution-based device fabrication onto flexible substrates with foreseeable avenues towards low-cost large-area printing techniques. This discussion will also review and identify the advantages and existing capabilities of tissue-equivalent materials in the detection of ionizing radiation as the ideal materials for in-vivo dosimetry. Finally, the radiation tolerance of organic materials is outlined to demonstrate that extensive investigations are still required before their utilization as radiation detectors.